How Sociology Perspective Influence Law with a Social Contexts? A Book Review â€œPokok-Pokok Sosiologi Hukumâ€, Prof Dr Soerjono Soekanto SH MA, Rajawali Pers, 269 Pages, ISBN 979-421-131-1 - Abraham, Abraham (Indonesian Journal of Advocacy and Legal Services, 2021)
sociology of law examines why humans obey the law and why it fails to obey the law and the social factors that influence it. as a relatively new branch of sociology, the science of legal sociology was developed to explain the interrelationships of patterns of behavior and law that cannot yet be explained by other branches of social science.